Rice microRNA1439 coordinates disease resistance and growth, represses the expression of OsRFPH2-6 and OsFLO2 - Kunquan, Liu; Zhixue, Wang; Tingcheng, Li; Weichen, Wang; Ziwei, Xiong; Changqing, Li; Dongyuan, Wang; Zhengwei, Wang; Changjian, Xu; Qianru, Lu; Wenjun, Dai; Feifei, Xu; et al. (Society for Experimental Biology, 2025)
Rice microRNA1439 (miR1439) belongs to a conserved miRNA family and its expression is induced by various biotic and abiotic stresses. However, whether and how miR1439 is involved in disease resistance in rice is unclear. In this study, we found that the expression of miR1439 was significantly upregulated upon Magnaporthe oryzae infection. Overexpressing miR1439 leads an enhanced disease resistance against M. oryzae, whereas blocking the function of miR1439 by overexpressing a target mimic resulted in increased disease susceptibility. Further investigation revealed that miR1439 directly targets and represses the expression of RING-H2 finger protein with potential E3 ligase activity (OsRFPH2-6), a negative regulator of disease resistance. Interestingly, transgenic lines blocking miR1439 exhibited increased grain length and grain weight, while overexpressing miR1439 leads a decreased grain length and grain weight, possibly due to the repression of FLOURY ENDOSPERM2 (OsFLO2), a target gene of miR1439. Thus, our findings highlight the pivotal role of miR1439 in mediating disease resistance and grain development in rice and provide a potential target for breeding resistant cultivars without yield penalty.